The relationship among oil and coal consumption, carbon dioxide emissions, and economic growth in BRICTS countries - Bildirici, Elif Melike; Bakirtas, Tahsin (AMER INST PHYSICS, 2016)
This study aims to analyze the relationship between carbon dioxide (CO2) emissions, economic growth, and coal and oil consumption in Brazil, Russia, India, China, Turkey, and South Africa by using the bounds test approach autoregressive distributed lag (ARDL) over the period from 1969 to 2011. According to ARDL analysis results, it is determined short-run and long-run relationships among selected variables. Three long-run estimators: ARDL cointegration, dynamic ordinary least squares, and fully modified ordinary least squares are utilized to test the robustness of the estimation results. The Granger causality and the forecast error variance decomposition approaches indicate the evidence of a causal relation between variables. According to empirical results, there are the evidence of a unidirectional Granger causality from real gross domestic product (GDP) to carbon dioxide (CO2) emissions in analyzed countries, uni-directional causality from coal consumption to carbon dioxide (CO2) emissions, uni-directional causality from oil consumption to carbon dioxide (CO2) emissions in China, India, Turkey, and South Africa and bi-directional causality in Brazil and Russia. Meanwhile, there is bidirectional causality from GDP to coal consumption, from coal consumption to oil consumption for Brazil, Russia, China, Turkey, and South Africa. India's causality results reveal a bidirectional causality from GDP to coal consumption, oil consumption, and carbon dioxide (CO2) emissions, and the results of forecast error variance supported the results of the causality test. Published by AIP Publishing.
Keywords: ENERGY-CONSUMPTION; CO2 EMISSIONS; ENVIRONMENTAL-QUALITY; POLLUTANT EMISSIONS; SOUTH-AFRICA; CHINA; INDIA; COINTEGRATION; CAUSALITY; INCOME; Science & Technology - Other Topics; Energy & Fuels